2017
DOI: 10.1021/acs.jafc.7b02531
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoids and Acarbose Synergistically Inhibit α-Glucosidase and Lower Postprandial Blood Glucose

Abstract: The inhibition of porcine pancreatic α-amylase and mammalian α-glucosidase by 16 individual flavonoids was determined. The IC values for baicalein, (+)-catechin, quercetin, and luteolin were 74.1 ± 5.6, 175.1 ± 9.1, 281.2 ± 19.2, and 339.4 ± 16.3 μM, respectively, against α-glucosidase. The IC values for apigenin and baicalein were 146.8 ± 7.1 and 446.4 ± 23.9 μM, respectively, against α-amylase. The combination of baicalein, quercetin, or luteolin with acarbose showed synergistic inhibition, and the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 52 publications
10
96
2
3
Order By: Relevance
“…On the other hand, the competitive inhibition against α-glucosidase of acarbose was demonstrated earlier. 26 Nonetheless, it should be noted that the levels of K m increment and V max reduction found in this study were only trivial in the presence of the LSA extract and acarbose, respectively. The inhibition constants (K i ) of both extracts against α-amylase were lower than that of acarbose.…”
Section: S117contrasting
confidence: 52%
“…On the other hand, the competitive inhibition against α-glucosidase of acarbose was demonstrated earlier. 26 Nonetheless, it should be noted that the levels of K m increment and V max reduction found in this study were only trivial in the presence of the LSA extract and acarbose, respectively. The inhibition constants (K i ) of both extracts against α-amylase were lower than that of acarbose.…”
Section: S117contrasting
confidence: 52%
“…A previous report identified C7G, E7G, and catechin in an ABE as antioxidants (Hori et al., ), and these compounds were shown to suppress antigen‐stimulated degranulation in leukemic cells (Itoh et al., ). Catechin has multiple biological functions, including the inhibition of α‐amylase and α‐glucosidase (Tadera et al., ), with the latter reported to occur via direct binding to the active site of α‐glucosidase (Zhang et al., ). Similarly to the previous reports, in this study, catechin showed inhibitory activity toward α‐amylase and α‐glucosidase (IC 50 values: α‐amylase, 0.30 mg/mL; α‐glucosidase, 0.033 mg/mL, data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…21 The IC 30 , IC 50 , and IC 70 values of myricetin were 1.12, 1.68, and 1.76 × 10 −6 mol L −1 , respectively, suggesting a strong inhibition against -glucosidase. Meanwhile, the values of IC 30 , IC 50 , and IC 70 of CRA were 11.3, 13.5, and 19.5 × 10 −6 mol L −1 .…”
Section: Isobolographic Analysis Of Combined Inhibitionmentioning
confidence: 94%
“…D X in the denominator is the dose that inhibits X% enzyme activity by single inhibitor. Based on the CI values, the interaction can be classified as synergism (CI < 0.9), addition (CI = 0.9–1.1), or antagonism (CI >1.1) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation